Effects of Fluoride on Respiration and Photosynthesis in Plants: An Overview - Krishna Kumar; Arup Giri; Prince Vivek; Kalaiyarasan T; Bhuvnesh Kumar (Annals of Environmental Science and Toxicology - Peertechz Publications, 2017)
Among all the halides, Fluoride (F) caused most severe adverse effects on plants through air, soil, and water, exposure. Besides the nutritional importance of this element, after its desirable limits in the plants, it caused adverse effects on plants through interfering with various physic-biochemical parameters; with or without any visible symptoms of injury. Due to higher level of fl uorides in plants, it also causes less development of plants through affecting several pathways associated with photosynthesis, respiration, protein synthesis, carbohydrate metabolism, and nucleotide synthesis. Photosynthesis and respiration are the most important process in the plants to acquire the basic energy and their utilization. Fluoride has great effective importance on these to pathways. On this view, the present review critically discusses the toxic effects on respiration and photosynthesis of agricultural crops and trees.